Hubungan Asosiasi antara Minat Belajar pada Mata Kuliah Kewirausahaan terhadap Minat Berwirausaha Mahasiswa Agribisnis Universitas Sultan Ageng Tirtayasa - Sudaesah, Lisa Apri; Prasetyo, Raffa Aryasatya Darrel; Ramadhan, Agim Mauzamma; Gunawan, Nuri Atikah; Nuralyasari, Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
From year to year population growth in Indonesia continues to increase. The increase in population and era changes that occur due to industrialization have created many new problems, one of which is unemployment. This is caused by an imbalance between the number of job seekers, the majority of whom are undergraduate graduates, and the number of job opportunities which are dwindling. In this situation, entrepreneurship is needed to create extensive job opportunities, not depend on other people and reduce unemployment by opening up job opportunities. Based on the results of pre-research observations on students from the Agribusiness Study Program at Sultan Ageng Tirtayasa University class of 2022, it shows that the majority of students are interested in becoming entrepreneurs, but there are still problems with entrepreneurial knowledge. Therefore, this research aims to test the effectiveness of the Entrepreneurship course on the Entrepreneurial Interest of Agribusiness Students at Sultan Ageng Tirtayasa University Class of 2022.